Advancing Prehospital Care: A Systematic Review Of Strategies For Developing Modern Ambulance Services (The Review of Diabetic Studies, 2025)
This systematic review explores global strategies and innovations driving the development of modern ambulance services, focusing on prehospital care enhancement, technological integration, and system-level reforms. The study examines how countries have advanced emergency response systems through digital transformation, workforce capacity-building, and inter-agency coordination. A structured review of literature from 2016 to 2025 identifies key success factors such as optimized dispatch models, evidence-based triage, data analytics, and cross-sector collaboration. The findings highlight the role of telemedicine, GPS-based navigation, and AI-supported decision-making in improving response times and patient outcomes. Furthermore, this review discusses the challenges in low-resource settings and proposes a conceptual framework for sustainable ambulance service development under national health transformation agendas. The study concludes with strategic recommendations to integrate innovation, quality management, and policy alignment to ensure equitable, timely, and high-quality prehospital care delivery.